Vespiform Thrips Franklinothrips vespiformis Crawford (Insecta:Thysanoptera: Aeolothripidae) - Runqian Mao; Yingfang Xiao; Steven P. Arthurs (EDIS, 2015)
Franklinothrips vespiformis Crawford is a predatory thrips with a pantropical distribution. The distinctive red, humped-back larvae and fast-moving ant-like adults are predaceous on small arthropods. In addition to being easily mistaken for an ant, this beneficial thrips is unusual in that it constructs a silken cocoon within which it pupates. Males of this species are rare. This species is sold for use as a biological control agent in botanical gardens, zoos, interior landscapes, research greenhouses, nurseries with ornamental plants as well as outdoors in subtropical regions. This 4-page fact sheet was written by Runqian Mao, Yingfang Xiao, and Steven P. Arthurs, and published by the UF Department of Entomology and Nematology, March 2015. (Photo credit: Runqian Mao, UF/IFAS)